TRIASSIC AND JURASSIC GASTROPODS FROM THE MISOOL ARCHIPELAGO, EASTERN INDONESIA - Hasibuan, Fauzie; Grant-Mackie, J.A (Pusat Survei Geologi, 2007)
The known gastropod fauna of Triassic and Jurassic ages from the Misool Archipelago is reviewed, based on collections made during a 1981 expedition jointly by personnel from the then-Geological Research and Development Centre, Bandung, and the Australian Bureau of Mineral Resources. The new material includes one new species, Bathrotomaria foronica, from the Yefbie Formation (Aalenian), and two undescribed but probably new species, a Rhaetian ?Angularia from the Lios Member of the Bogal Formation and a Purpurina of Aalenian or jBajocian age from the Yefbie Formation. In addition, other material from the Rhaetian Lios Member, too poorly preserved for generic identification, is allotted to the Subfamily Neritinae. Some forms recorded by earlier workers were not recollected but have been listed for completeness, giving a total of five described species and a further five in open nomenclature. Most taxa are unique to this area, but one, Eucyclus orbignyanus (Hudleston), is known also from Europe. Keywords: gastropod, Triassic, Jurassic, Misool Archipelago, Yefbie Formation, Lios Member, Bogal Formation